The Granular Trade and Production Activities (GRANTPA) database - Sebastien Bradley; Javier Flórez Mendoza; Mario Larch; Yoto Yotov (The Vienna Institute for International Economic Studies (wiiw), 2024)
This paper introduces the Granular Trade and Production Activities (GRANTPA) database, which covers international trade flows for 3,124 products and 247 countries over the period 1995-2019 as well as domestic trade flows and production data for the same number of products and years for a subset of 35 European economies. The original data sources that we employ are Eurostat's Comext and Prodcom databases. A gravity application delivers a large set of product-level 'home bias' estimates, which cannot be obtained without domestic trade flows. The average estimates on the standard gravity variables in our model (e.g., distance) are comparable to those from the related literature. However, our disaggregated estimates are very heterogeneous across products, thus highlighting the importance of our new database.
Keywords: C81; F13; F14; 330; Gravity Data; Structural Gravity; Domestic Trade Flows; Disaggregated Gravity Estimates; Home Bias Estimates